epsilon-Expansion for nonplanar six-propagators double boxes - Suzuki, Alfredo T.; Schmidt, Alexandre G. M. (Natl Research Council Canada, 2006)
We present calculations for a nonplanar double box with four massless, massive external, and internal legs propagators. The results are expressed for arbitrary exponents of propagators and dimension in terms of Lauricella's hypergeometric functions of three variables and hypergeometric-like multiple series.